2021
DOI: 10.3389/pore.2021.580800
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase is Associated With Prognosis and Response to Chemotherapy in Advanced Gastric Cancer

Abstract: Background: Cholinesterase (CHE) is a routine serum biomarker in gastric cancer (GC). However, little research has been done on its clinical value in advanced GC. In addition, it is not clear whether it can be used as biomarker for the response and prognosis of advanced GC patients.Methods: Between Jan. 2013 and Dec. 2016, a total of 150 patients with advanced GC treated with first-line chemotherapy were admitted to Changzhou Tumor Hospital Affiliated to Soochow University. We retrospectively identified serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Various studies have validated sCHE as a marker of nutritional status, correlating low sCHE levels to sarcopenia and to a high nutritional risk in critically ill patients treated on ICUs [ 26 , 41 , 42 ]. Beside the critically ill, oncologic patients are another group for which malnutrition importantly influenced postoperative morbidity and mortality [ 43 , 44 ]. In patients with colorectal cancer, low sCHE levels were associated with poor 5-year overall and disease-specific survival rates [ 43 ], whereas nutritional support led to an increase in sCHE levels and in body weight [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have validated sCHE as a marker of nutritional status, correlating low sCHE levels to sarcopenia and to a high nutritional risk in critically ill patients treated on ICUs [ 26 , 41 , 42 ]. Beside the critically ill, oncologic patients are another group for which malnutrition importantly influenced postoperative morbidity and mortality [ 43 , 44 ]. In patients with colorectal cancer, low sCHE levels were associated with poor 5-year overall and disease-specific survival rates [ 43 ], whereas nutritional support led to an increase in sCHE levels and in body weight [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, serum cholinesterase levels can be used to evaluate the severity and prognosis of the disease and is a useful clinical indicator. A variety of malignancies have bad prognoses when cholinesterase levels are reduced, such as prostate cancer (47) colorectal cancer (48) non-small cell lung cancer (49) carcinoma of stomach (50). It is crucial in determining which illnesses are benign and which ones are malignant.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research suggests that expression of cholinesterase is associated with response to chemotherapy in cancer patients [ 30 ]. For example, lower ChE level may predict a poorer prognosis for biliary tract cancer patients received chemotherapy of gemcitabine and cisplatin [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower ChE level may predict a poorer prognosis for biliary tract cancer patients received chemotherapy of gemcitabine and cisplatin [ 31 ]. Another newly published study revealed the potential value of ChE as a real-time indicator of chemotherapy performance [ 30 ]. A reasonable explanation behind this result could be that ChE was associated with multiple conditions, particularly liver function and malnutrition which are generally related to chemotherapy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%